If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+8=(-5x)+5
We move all terms to the left:
4x+8-((-5x)+5)=0
We calculate terms in parentheses: -((-5x)+5), so:We get rid of parentheses
(-5x)+5
We get rid of parentheses
-5x+5
Back to the equation:
-(-5x+5)
4x+5x-5+8=0
We add all the numbers together, and all the variables
9x+3=0
We move all terms containing x to the left, all other terms to the right
9x=-3
x=-3/9
x=-1/3
| x/10=5x= | | 4x+8=-5x+5 | | 2u=1=9 | | x/12+1=2 | | 10y+3=10y+3 | | 119=y-14 | | 10y+3=10y+5 | | x/7-2/14=(6+5x)/7+(6+2x)/1 | | 10y=14y | | 2(2y+8)+y=71 | | 3x-12=-1x+28 | | 2y+y=71 | | -16v=0 | | (49/81)^x=1 | | -2=n/3+4 | | (t+2)^2+(t-1)^2=9 | | 30-l=44 | | s-35=19 | | 18x-14=8+4-4 | | 3x-32+2x+26=180 | | 2(m+4)=-12 | | 7x+1/2=2(3x+1) | | z+23=6 | | 0=-2(6+x-16 | | 6/x+1=2 | | 12=7x+4(3-x | | 4y+13=22 | | 4x+3(2-x)=12 | | ?+2x?=402 | | 7c+6c×8-3c=1 | | 3p+20+2p+20=180 | | 2y+15=3y−35. |